Urgensi Akta Kematian Dalam Proses Pewarisan Di Kota Bukittinggi Sumatera Barat - Rahma Yulia; Helfira Citra (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
Inheritance is the transfer of assets from a deceased person to their heirs, and their use to improve the welfare of surviving family members and improve their lives. This means that all rights and responsibilities of the deceased are fully transferred to the heirs or other individuals entitled to the transfer. This document is a crucial type of population administration document, as without it, other population administration processes can be hampered. Presidential Regulation Number 25 of 2008 concerning Requirements and Procedures for Registering Residents and Civil Registration, in Article 1 paragraph (10) explains that "Population events refer to every event experienced by citizens that needs to be reported because it can affect the issuance of a resident identity card, or other population documents. The formulation of the problem raised in this study is: (1) how urgent is the death certificate according to Indonesian civil law in the inheritance process?; (2) what is the impact that arises when there is a delay in issuing a death certificate in the inheritance process? The purpose of this study is to find out and understand the urgency of a death certificate according to Indonesian civil law in the inheritance process and to find out the impact of the delay in issuing a death certificate on the inheritance process. This study uses a normative juridical method by examining laws and regulations and a case approach with data collection techniques through literature studies of laws and regulations, legal literature. The conclusion is that recording death in the form of a death certificate to fulfill legal certainty. Legal certainty has a big influence on a law that If legal certainty is met, the law is considered to be in effect.